<span>∫(sinx cosx)^2dx = ∫(1/2sin 2x)^2 dx = 1/4∫sin^2 2x dx = 1/4∫1/2(1 - cos 4x)dx = 1/8∫(1 - cos 4x) dx = 1/8[x - sin 4x / 4] + c = 1/32(4x - sin 4x) + c
</span>
<h2>
Answer:</h2><h2>The expressions that can be subtracted from 9x to result in the expression 3x+5 is 6x - 5</h2>
Step-by-step explanation:
To find the expression that can be subtracted from 9x to result in the expression 3x+5.
Let us consider the expression, a - b = c
Here a = 9x
the result, c = 3x + 5
b = ?
Substitute the values in the above equation, we get
9x - b = 3x + 5
9x - (3x + 5) = b
b = 6x - 5
2πrh= S
π = S/(2rh)
the answer to the question
Let the width =x
length = 6x
p=14x
28=14x
x=2